Indigenous Participation in Australian Economies II Historical engagements and current enterprises - Fijn, Natasha; Keen, Ian; Lloyd, Christopher; Pickering, Michael (ANU Press, 2012)
This is the second volume to emerge from a project on Indigenous participation in the Australian economy, funded by an Australian Research Council (ARC) Linkage Grant, and involving the cooperation of the School of Archaeology and Anthropology at The Australian National University and the National Museum of Australia. The Chief Investigators were Ian Keen, Chris Lloyd, Anthony Redmond, the Partner Investigator was Mike Pickering, Fiona Skyring was an associate researcher on the project, and Natasha Fijn was research assistant. The present volume arises out of a conference in Canberra on Indigenous Participation in Australian Economies at the National Museum of Australia on 9-10 November 2009, which attracted more than thirty presenters. The diverse themes included histories of economic relations, the role of camels and dingoes in Indigenous-settler relations, material culture and the economy, the economies of communities from missions and stations to fringe camps and towns, the transitions from payment-in-kind to wage economies and Community Development Employment Projects, the issue of unpaid and stolen wages, local enterprises, and conflicts over development. Sixteen of those papers have been developed as chapters in this volume, together with a foreword by Professor Jon Altman. This book comprises a companion volume to Indigenous Participation in Australian Economies: Historical and Anthropological Perspectives, published by ANU E Press in 2010.